Optimalisasi Kandungan Nutrisi Tepung Limbah Pembuatan Kerupuk Sanjai melalui Fermentasi dengan Ragi Sebagai Bahan Ransum Itik Alternatif - Zasmeli Suhaemi (Fakultas Pertanian Universitas Tamansiswa Padang, 2010)
This research was conducted to examine the effect of fermentation Sanjai’s waste meal by Yeast. The research wast to looking for best fermentation of Sanjai chip’s waste by Yeast with three level inoculum (1%, 2% and 3%) as factor A, and three long fermentation time (4, 5, and 6 days) as factor B, for gotten best crude protein of product. Its used Completed Randomized Design in factorial 3 X 3 with two replications. There was three variabels on this research;1 Crude Protein content), 2)Crude Fiber content, and 3) Dry content. The best crude protein of fermentation Sanjai’s waste meal found by using inoculum level on 3%, with time of fermentation six days. It increse from 5,02% to 9,13 % or increase 75% from base.